Polo-like kinase 2: A new exploitable target to undermine mutant p53-dependent chemoresistance - Napoli, Marco (2012)
During the last decade, the role of p53 point mutants as determinants of tumor aggressiveness was conclusively demonstrated.1 Based on a large body of evidence, a more complete picture on the consequences of p53 mutation in human cancer is emerging, where a single missense mutation transforms one of the most efficient tumor suppressor pathways into a powerful network promoting tumor progression. Indeed, these mutant p53 proteins are devoid of oncosuppressive abilities while, on the contrary, acquire novel oncogenic properties supporting several tumorigenic processes like cell proliferation, death resistance, genomic instability, angiogenesis and metastasis formation.